First record of spiral fovea amphidialis in Acantholaimus (Chromadoridae: Nematoda), with a description of a new species from shallow sediments of the South Atlantic and an emended diagnosis of the genus - Manoel, Alex; Silva, Maria Cristina Da; Esteves, André M. (Zootaxa, 2017)
A new species of the genus Acantholaimus is described from the South Atlantic, in the Potiguar Basin off the continental shelf of northeast Brazil. Acantholaimus marliae sp. n. is characterized by the long body; numerous somatic setae arranged in four sublateral longitudinal rows; buccal cavity with five solid teeth (four subventral and one dorsal), with the largest tooth dorsally located and the most protuberant between the subventral teeth shaped similarly to a "bottle opener"; and spiral fovea amphidialis. Acantholaimus marliae sp. n. is the only species described for the genus that has a spiral fovea amphidialis. This is the fifth species of Acantholaimus described from shallow water. An emended diagnosis of the genus is provided.